Evaluation of perfusion parameters of gingival inflammation using laser Doppler flowmetry and tissue spectrophotometry- a prospective comparative clinical study - Marie Sophie Katz; Mark Ooms; Philipp Winnand; Marius Heitzer; Anna Bock; Kristian Kniha; Frank Hölzle; Ali Modabber (BMC, 2023)
Abstract Background The aim of this study was to determine the values of different perfusion parameters- such as oxygen saturation, the relative amount of hemoglobin, and blood flow- in healthy subjects compared to patients with gingivitis as a non-invasive measurement method. Methods A total of 114 subjects were enrolled in this study and separated into subjects with gingivitis (50) and without gingivitis (64) based on clinical examination. Gingival perfusion was measured at 22 points in the maxilla and mandible using laser Doppler flowmetry and tissue spectrophotometry (LDF-TS) with the "oxygen to see" device. All patients underwent measurement of gingival perfusion, followed by the clinical evaluation (measurement of probing depths, evaluation of bleeding on probing, plaque level, and biotype). Perfusion parameters were compared between the groups, associations between the non-invasive and clinical measurements were analyzed, and theoretical optimal cut-off values for predicting gingivitis were calculated with receiver operating characteristics. Results The mean oxygen saturation, mean relative amount of hemoglobin, and mean blood flow all significantly differed between the groups with and without gingivitis (p = 0.005, p < 0.001, and p < 0.001, respectively). The cut-off value for predicting gingivitis was > 40 AU (p < 0.001; sensitivity 0.90, specificity 0.67). Conclusions As a non-invasive method, LDF-TS can help determine gingival hyperemia. Flow values above 40 AU indicate a higher risk of hyperemia, which can be associated with inflammation. The LDF-TS method can be used for the objective evaluation of perfusion parameters during routine examinations and can signal the progression of hyperperfusion before any change in clinical parameters is observed. Trial registration All procedures performed in this study involving human participants were in accordance with the ethical standards of the institutional and/or national research committee and with the 1964 Helsinki Declaration and its later amendments or comparable ethical standards. The study was approved by the institutional Clinical Research Ethics Committee (Ethik-Kommission der Medizinischen Fakultät der RWTH Aachen, Decision Number 286/20) and retrospectively registered by the German Clinical Trials Register (File Number DRKS00024048, registered on the 15th of October 2021).